2002
DOI: 10.1021/la011596m
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cholesterol, Lanosterol, and Ergosterol on Lecithin Bilayer Mechanical Properties at Molecular and Microscopic Dimensions:  A Solid-State NMR and Micropipet Study

Abstract: Lecithin (DPPC) membranes doped with high concentrations (40 mol %) of three biologically relevant sterols (cholesterol, lanosterol, and ergosterol) were studied by spectroscopic and force measurements. Micropipet aspiration measurements of giant unilamellar vesicles provided the membrane area expansion modulus K on the microscopic scale while deuterium NMR experiments gave parameters such as the line shape, transverse relaxation, and molecular order, which are all based on a molecular scale at a given time re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
64
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(81 citation statements)
references
References 17 publications
(26 reference statements)
15
64
2
Order By: Relevance
“…(5), the area compressibility modulus KA can be calculated as 306, 402, and 760 mN/m, respectively. KA increases with the increase of the cholesterol concentration, which is in qualitative agreement with that observed from experiments (Endress et al, 2002;Needham and Nunn, 1990). Using these parameters A0, KA, and c in Fig.…”
Section: Estimation Of Line Tensionsupporting
confidence: 90%
“…(5), the area compressibility modulus KA can be calculated as 306, 402, and 760 mN/m, respectively. KA increases with the increase of the cholesterol concentration, which is in qualitative agreement with that observed from experiments (Endress et al, 2002;Needham and Nunn, 1990). Using these parameters A0, KA, and c in Fig.…”
Section: Estimation Of Line Tensionsupporting
confidence: 90%
“…This result is consistent with the reduction in orientation observed for egg phosphatidylcholine (PC)/Chol (Qiu et al, 1993) but conflicts with the increased magnetic alignment observed for a DPPC/Chol system (Brumm et al, 1992;Reinl and Bayerl, 1992;Endress et al, 2002) Measurements of the elastic area compressibility modulus, K m (proportional to Ä, Eq. (1)) by micromechanical techniques of SM and saturated PC GLVs with 50 mol% Chol (McIntosh et al, 1992) reveal K m values more than 2.3 larger (perhaps reflecting increased cholesterol association) than those reported for DPPC/40 mol% Chol (Endress et al, 2002). It is possible the increased membrane curvature energy for SM/Chol and PC/Chol bilayers suppresses the degree of magnetic deformation in these systems.…”
Section: Effect Of Temperature On Magnetic Alignment For Sm In Mlvssupporting
confidence: 73%
“…In addition, conflicting results have been reported for mixed phospholipid/cholesterol systems. For DPPC/30% Chol, the degree of magnetic alignment increases as cholesterol is added (Brumm et al, 1992;Reinl and Bayerl, 1992;Endress et al, 2002). However, for an egg PC liposome, a decrease in the percent of aligned phospholipids was observed when 30% cholesterol was added above T m (Qiu et al, 1993).…”
Section: Introductionmentioning
confidence: 98%
“…In terms of biomolecular NMR spectroscopy, it has been observed that the slope of square-law plot is greater for lanosterol than for cholesterol, consistent with the bilayer stiffness being less for lanosterol versus its metabolic product cholesterol (Martinez et al, 2004; Orädd et al, 2009; Shahedi et al, 2006). Again, it is found that the site-specific analysis of the solid-state NMR results based on atomistic observables matches the results for the macroscopic bilayer elasticity (Endress et al, 2002a; Endress et al, 2002b) (Fig. 9).…”
Section: Nuclear Spin Relaxation Reveals Multiscale Dynamics Of Membrsupporting
confidence: 72%